MEMPROGRAMKAN PENGENALAN AKUNTANSI SYARIAH BAGI USAHA MIKRO MENENGAH DESA BOJONG JENGKOL, KECAMATAN CIAMPEA, BOGOR - Rully Trihantana; Ria Kusumaningrum; Siti Mirnawati (SAHID DEVELOPMENT JOURNAL, 2022)
Micro, Small and Medium Enterprises are the most important pillars of the Indonesian economy.Based on data from the Ministry of Cooperatives and Micro and Medium Enterprises in the firstquarter of 2021, the number of Small and Medium Enterprises in Indonesia reached 64.2 million.Contribution to GDP reached 61.07% or Rp 8,573.89 trillion. Micro, Small and MediumEnterprises or MSMEs can also absorb 97% of the total workforce and collect 60.4% of the totalinvestment. However, good financial records are needed for MSMEs so that the process ofbusiness continuity is getting better. Therefore, community service for MSMEs is carried out inBojong Jengkol Village, Ciampea District, Bogor Regency, moreover there are still few whounderstand the importance of financial records in order to formulate strategies. The purpose ofthis activity is to help MSMEs understand more about accounting records, the importance ofaccounting records, and the application of effective and efficient records. With this activity, it ishoped that MSMEs can be motivated to make financial records, and can even make financialreports for financing applications, and to evaluate their business performance.